Pyruvate Might Bridge Gut Microbiota and Muscle Health in Aging Mice After Chronic High Dose of Leucine Supplementation - Liao, Yuxiao; Li, Dan; Zhou, Xiaolei; Peng, Zhao; Meng, Zitong; Liu, Rui; Yang, Wei (Frontiers in Medicine, 2021)
Background: Previous studies demonstrated that there might be complex and close relationships among leucine supplementation, gut microbiota and muscle health, which still needs further investigation. Aims: This study aimed to explore the associations of gut microbiota with muscle health after leucine intake. Methods: Nineteen-month-old male C57BL/6j mice (n = 12/group) were supplemented with ultrapure water, low dose of leucine (500 mg/kg·d) and high dose of leucine (1250 mg/kg·d) for 12 weeks by oral gavage. Mice fecal samples in each group before and after supplementation were collected for baseline and endpoint gut microbiota analysis by 16S rDNA amplicon sequencing. Meanwhile, ultrasound measurement, H&E staining, myofiber cross-sectional area measurement and western blotting were performed in the quadriceps subsequently. Pyruvate levels were detected in feces. Results: Improvement in muscle of histology and ultrasonography were observed after both low and high dose of leucine supplementation. High dose of leucine supplementation could promote skeletal muscle health in aging mice via regulating AMPKα/SIRT1/PGC-1α. The richness and diversities of microbiota as well as enriched metabolic pathways were altered after leucine supplementation. Firmicutes-Bacteroidetes ratio was significantly decreased in high-leucine group. Moreover, pyruvate fermentation to propanoate I were negatively associated with differential species and pyruvate levels were significantly elevated in feces after high dose of leucine supplementation. Conclusions: Chronic high dose of leucine supplementation changed gut microbiota composition and increased pyruvate levels in feces, which possibly provides a novel direction for promoting muscle health in aging mice.